Galectin-1 and Its Involvement in Hepatocellular Carcinoma Aggressiveness - Spano, Daniela (ScholarOne, 2010)
Hepatocellular carcinoma is one of the most common cancers worldwide. Despite several efforts to elucidate hepatocellular carcinoma molecular pathogenesis, it is still not fully understood. To acquire further insights into the molecular mechanisms of hepatocellular carcinoma, we performed a systematic functional genomic approach on human HuH-7 and JHH-6 cells. The subsequent analysis of the differentially expressed genes in human specimens revealed a molecular signature of 11 genes from which we selected the LGALS1 gene, which was overexpressed in hepatocellular carcinoma. The expression analysis in humans of Galectin-1 (Gal-1), the protein encoded by LGALS1, showed a Gal-1 preferential accumulation in the stromal tissue around hepatocellular carcinoma tumors. Moreover, a significant association between increased expression of Gal-1 in hepatocellular carcinoma and the presence of metastasis was observed. Interestingly, Gal-1 overexpression resulted in an increase of cell migration and invasion. In conclusion, this study provides a portfolio of targets useful for future investigations into molecular marker–discovery studies on a large number of patients and functional assays. In addition, our data provide evidence that Gal-1 plays a role in hepatocellular carcinoma cell migration and invasion, and we suggest that further studies should be conducted to fully establish the role of Gal-1 in hepatocellular carcinoma pathogenesis and evaluate Gal-1 as a potential molecular therapeutic target.